2019
DOI: 10.1002/da.22897
|View full text |Cite
|
Sign up to set email alerts
|

A placebo‐controlled pilot study of a wearable morning bright light treatment for probable PTSD

Abstract: Background: Evidence-based treatments for post-traumatic stress disorder (PTSD) have poor uptake and remission rates, suggesting that alternative treatments are needed. Morning bright light may be an effective treatment for PTSD given its established effects on mood and sleep, however, there are no published trials. Methods:We conducted a placebo-controlled pilot trial of a wearable light device, the Re-timer ® , for individuals with probable PTSD. Individuals were randomly assigned to the active Re-timer ® (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Furthermore, while such behavioral and motivational barriers to adherence are presumed, they have not been systematically assessed and characterized. Relatedly, methods for effectively tracking adherence to light therapy remain limited (although see [ 15 ] for one promising approach). Furthermore, the patient’s subjective experience should be considered when evaluating treatment success, and this has been lacking in prior research [ 16 ].…”
Section: Overall Gaps Across All Crswdmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while such behavioral and motivational barriers to adherence are presumed, they have not been systematically assessed and characterized. Relatedly, methods for effectively tracking adherence to light therapy remain limited (although see [ 15 ] for one promising approach). Furthermore, the patient’s subjective experience should be considered when evaluating treatment success, and this has been lacking in prior research [ 16 ].…”
Section: Overall Gaps Across All Crswdmentioning
confidence: 99%
“…Although the pathophysiology in both ASWPD and DSWPD is hypothesized to be due to a misaligned circadian phase [ 19 ], recent studies that have measured phase in patients with ASWPD and DSWPD have found that an altered circadian phase may not always be present [ 6 , 8 , 19 ], and the sleep timing may be advanced or delayed without a corresponding shift in the underlying circadian timing. For example, two groups have independently found that DSWPD patients can be broadly dichotomized into two distinct subtypes based on their endogenous circadian phase [ 6 , 15 ]: those patients with both delayed sleep and delayed endogenous circadian phase ( Figure 3 , A ), and those with delayed sleep but without a delayed endogenous circadian phase ( Figure 3 , C ). These recent findings highlight that there must be multiple underlying mechanisms driving the delayed sleep phenotype.…”
Section: Phase Disordersmentioning
confidence: 99%
“…In addition, cognitive-behavioural social rhythm group therapy have been also found to have positive effects on SD in veterans with PTSD (Haynes et al, 2016 ), supporting the importance of circadian synchronization in the treatment of the disorder. Interestingly, a recent placebo-controlled pilot study assessing morning bright light treatment in PTSD through a wearable device has also demonstrated efficacy in reducing PTSD symptoms (Zalta, Bravo, Valdespino‐Hayden, Pollack, & Burgess, 2019 ). Finally, there are some reports that posttraumatic sleep deprivation in the immediate aftermath (i.e., first night) of the trauma, can lead to reduced stress responses in the future, possibly by re-synchronizing the circadian and stress system (Cohen, Kaplan, Zohar, & Cohen, 2017 , Cohen et al, 2012 ).…”
Section: Chronotherapeutic Implications For Posttraumatic Chronodisrumentioning
confidence: 99%
“…Cognitive-behavioural sleep management and social rhythm group therapy constitute an acceptable and effective treatment option in PTSD (Epstein, Babcock-Parziale, Haynes, & Herb, 2012 ; Haynes et al, 2016 ; Margolies, Rybarczyk, Vrana, Leszczyszyn, & Lynch, 2013 ; Schoenfeld, Deviva, & Manber, 2012 ; Talbot et al, 2014 ). Interestingly, two recent studies also support the efficacy of morning bright light treatment in reducing overall PTSD symptoms (Youngstedt et al, 2021 ; Zalta, Bravo, Valdespino‐Hayden, Pollack, & Burgess, 2019 ), supporting the importance of circadian synchronization in the treatment of the disorder. Finally, there are first findings for an additional prevention potential of chronobiological measures (e.g.…”
Section: Future Perspectivesmentioning
confidence: 90%